158k views
0 votes
5^(-7)*5^(12)*5^(-2)

with steps

User Shamese
by
5.3k points

2 Answers

6 votes

Answer:

125

Explanation:

in any exponential multiplication, the exponents add together

x^y X x^y = x^2y

so 5^-7 X 5^12 X 5^-2 is equal to 5^(-7+12-2) = 5^3

5^3 = 5 X 5 X 5 = 25 X 5 = 125

User Swati Garg
by
6.0k points
7 votes

Answer:

=125

Explanation:

5−7)(512)(5−2)

=

1

78125

(512)(5−2)

=

1

78125

(512)(5−2)

=(

1

78125

(244140625))(5−2)

=3125(5−2)

=3125(

1

25

)

=125

User Brijesh Patel
by
5.6k points